Marvelous Bookcase: Yang Jiong’s “Fu on the Bookcase for Reading While Lying Down” - Miao, Xiaojing (Journal of the American Oriental Society, 2023)
Yang Jiong 楊炯 (650–ca . 694), though hailed both by his contemporaries and later generations as one of the “Four Elites of the Early Tang,” has yet to receive due scholarly attention. This article contributes to the study of Yang Jiong by examining his “Fu on the Bookcase for Reading While Lying Down” (“Wodu shu- jia fu” 臥讀書架賦). It demonstrates how the poet displays his literary genius by skillfully employing various allusions, using self-deprecating humor for assertive self-display, devising close echoes among different parts, and building an extremely well-balanced structure, written in verse of an elaborately parallel style. More importantly, he cleverly crafts a double text so that both the physical bookcase and he himself, the “mental bookcase,” become the dual subjects of the fu. The interplay between the bookcase, the poet, and his self-representation also contributes to the wider discussions of material culture, social norms, and literary expression.